Circulating Levels of Angiotensinogen, Sex Hormones, and Hormone Therapy—The Multi‐Ethnic Study of Atherosclerosis (MESA) - Karita C. F. Lidani; Patrick J. Trainor; Robert Buscaglia; Kristoff Foster; Sophia Jaramillo; Kirolos Michael; Alexander P. Landry; Erin D. Michos; Pamela Ouyang; Erin S. Morgan; Sotirios Tsimikas; Andrew P. DeFilippis (The Journal of Clinical Hypertension, 2025)
ABSTRACT Angiotensinogen, the unique precursor of all angiotensin hormones of the renin‐angiotensin‐aldosterone system (RAAS), is now a potential target in a novel pharmacological approach to hypertension. Investigating the factors that influence angiotensinogen levels, including sex hormones, may have important therapeutic implications. Plasma angiotensinogen and sex hormones levels were measured in 5171 Multi‐Ethnic Study of Atherosclerosis (MESA) participants. Linear models were employed to determine the associations of angiotensinogen with sex hormones. Angiotensinogen levels were significantly higher in postmenopausal women receiving hormone therapy (HT, n = 760) compared to women not receiving HT (n = 1675) and in men (n = 2736). A positive association was present between angiotensinogen and estrogen levels that differed in magnitude between sexes and by HT status among postmenopausal women (women on HT: r = 0.44, p < 0.0001; women not on HT: r = 0.09, p = 0.0002; and men: r = 0.07, p = 0.0003). The type of HT formulation (estrogen or estrogen/progesterone) and its duration of use did not significantly affect angiotensinogen levels. This study suggests a significant role of sex, estrogen, and HT in the pathophysiology of angiotensinogen, which is important given the development and testing of angiotensinogen‐targeting therapeutics.